Prioritarianism in Practice - Basu, Kaushik (Journal of Economic Literature, 2023)
Kaushik Basu of Cornell University reviews “Prioritarianism in Practice” edited by Matthew D. Adler and Ole F. Norheim. The Econlit abstract of this book begins: “Twelve papers explore the use of prioritarianism as a methodology for evaluating governmental policy, highlighting the value of giving extra weight to the well-being of the worse off in policy assessment across a variety of domains.”